The tragedies of Algernon Charles Swinburne - Swinburne, Algernon Charles (Chatto, 1905)
[V.1] The queen mother and Rosamond -- [V.2] Chastelard and Bothwell (Acts I-II) :- Act I-David Rizzio -- Act II - Bothwell -- [V.3] Bothwell (Act III- V) :- Act III- Jane Gordon -- Act IV- John Knox -- Act V- The Queen -- [V.4] Mary Stuart -- [V.5] Locrine, The sisters, Marino Faliero, Rosamund queen of the lombards